New CO2 capturing cement - Loi, Jing Ying (Nanyang Technological University, 2021)
In this report, studies on Reactive Magnesium Oxide Cement (RMC) will be conducted, looking into detail its process of hydration and carbonation. In addition, industrial by-product Granulated Blast Furnace Slag (GGBS) will be added to partially substitute RMC. This is because MgO was found to be a suitable alkaline activator of GGBS, and with this partial replacement of RMC with GGBS, the RMC production cost can be lowered as well to be more cost-effective and at the same time more environmentally-friendly. In view of accelerating hydration, high temperature pre-curing (HTPC) will be implemented. To aid in the carbonation of MgO hydration products, an innovative method – microbial induced carbonate precipitation (MICP) – will be carried out, in which urea and bacteria will be mixed into the sample for subsequent carbonation reaction to occur after hydration of MgO. With increased hydration from dissolution of MgO, more brucite will be formed to increase chances to undergo carbonation and form hydrated magnesium carbonates (HMCs). GGBS activated by MgO will undergo hydration to form products like hydrotalcite and this will also be presented in this report. Both HMCs and hydrotalcite provides the overall strength developments to the concrete mix. Detailed analysis of microstructural properties will also be carried out through XRD, TG-IR and SEM. Results have shown that elevated pre-curing temperature have increased MgO dissolution and hence more brucite being formed. MICP has successfully allowed carbonation to take place in the samples and overall mechanical strength have shown that samples with addition of both urea and bacteria with GGBS reflects the highest compressive strength within each temperature group tested.